2016
DOI: 10.1093/cz/zow112
|View full text |Cite
|
Sign up to set email alerts
|

Loss of largest and oldest individuals of the Montpellier snake correlates with recent warming in the southeastern Iberian Peninsula

Abstract: The effects of climate change on organisms are now being extensively studied in many different taxa. However, the variation in body size, usually shrinkage in response to increasing temperature, has received little attention regarding to reptiles. During past periods of global warming, many organisms shrank in size, and current evidence and experiments manipulating temperature have shown a biomass decrease in some organisms with increasing temperatures. Here we test whether the body size of the Montpellier sna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Recent decreases in body size of ectotherms are often explained by the general negative relationship between adult body size and temperature in relation to climate warming (Gardner, Peters, Kearney, Joseph, & Heinsohn, ; Scheffers et al, ; Sheridan & Bickford, ). It was shown that increasing temperature caused decreases in the body size over several decades in butterflies (Bowden et al, ), beetles (Tseng et al, ), fishes (Baudron, Needle, Rijnsdorp, & Tara Marshall, ; Daufresne, Lengfellner, & Sommer, ), amphibians (Caruso, Sears, Adams, & Lips, ; Reading, ; Sheridan, Caruso, Apodaca, & Rissler, ), and reptiles (López‐Calderón, Feriche, Alaminos, & Pleguezuelos, ). In a frog, Lithobates sylvaticus , and a few species of salamanders, the magnitude and the direction of the body size response differed geographically, and depended on the change in temperature and precipitation (Caruso et al, ; Sheridan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent decreases in body size of ectotherms are often explained by the general negative relationship between adult body size and temperature in relation to climate warming (Gardner, Peters, Kearney, Joseph, & Heinsohn, ; Scheffers et al, ; Sheridan & Bickford, ). It was shown that increasing temperature caused decreases in the body size over several decades in butterflies (Bowden et al, ), beetles (Tseng et al, ), fishes (Baudron, Needle, Rijnsdorp, & Tara Marshall, ; Daufresne, Lengfellner, & Sommer, ), amphibians (Caruso, Sears, Adams, & Lips, ; Reading, ; Sheridan, Caruso, Apodaca, & Rissler, ), and reptiles (López‐Calderón, Feriche, Alaminos, & Pleguezuelos, ). In a frog, Lithobates sylvaticus , and a few species of salamanders, the magnitude and the direction of the body size response differed geographically, and depended on the change in temperature and precipitation (Caruso et al, ; Sheridan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Large and presumably old individuals are essential for population viability in long-lived reptiles with indeterminate growth, notably because reproductive output and survival probability increase with body size [52]. Both snake species (M. monspessulanus and Z. scalaris) are long-lived animals (>14 years) [40] with delayed maturity and relatively low fecundity [31]. The sharp decline in M. monspessulanus snake numbers in Port-Cros is worrying, adult numbers will decrease if wild boar pressure is not relaxed, therefore entailing population collapse.…”
Section: Discussionmentioning
confidence: 99%
“…Juveniles and adults were distinguished according to their size (snout to vent length, SVL) and/or using information on their reproductive status when available (i.e., presence of eggs) [32]. The size at which individuals attain maturity varies according to species and sex, we used the following criteria: juvenile (SVL < 55 cm) in male of M. monspessulanus, and females SVL < 65 cm [40]. All individuals were rapidly released at the exact place of capture.…”
Section: Snake Population Monitoringmentioning
confidence: 99%
“…Sexual size dimorphism may drive sex-specific decline in body size, due to higher pressure on larger specimens (López-Calderón et al 2017 ; Bury and Zając 2020 ). At the whole population level, size-biased pressure can result in changes of sex ratio.…”
Section: Introductionmentioning
confidence: 99%